The Influence of Activated Carbon Produced from Duck Eggshells as an Adsorbent for Free Fatty Acid Content of Used Cooking Oilc - Barita Aritonang; Ahmad Hafizullah Ritonga; Karnirius Harefa; Herlina Herlina; Dicky Yuswardi Wiratma (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
The repeated use of cooking oil can lead to a decline in oil quality and an increase in free fatty acid (FFA) levels, which may pose adverse health effects when consumed continuously. Therefore, an effective, safe, and sustainable purification method is required to improve the quality of used cooking oil. This study aims to evaluate the effectiveness of activated carbon derived from duck eggshell waste in reducing FFA levels in used cooking oil. The research employed a laboratory experimental method with a post-test only control group design. Samples of used cooking oil were selected purposively based on a level of degradation representative of real conditions. The preparation of activated carbon began with the carbonisation of duck eggshells, followed by chemical activation using a 3 M phosphoric acid (H₃PO₄) solution to enhance surface area and adsorbent porosity. The resulting activated carbon was then applied in the adsorption process of used cooking oil. FFA levels were analysed using the alkalimetric titration method. The results showed that the activated carbon significantly reduced FFA levels from 1.57% to 0.22%, with a reduction efficiency of 75%. This final value complies with the quality standard for cooking oil according to SNI 3741:2013 (≤0.3%). Furthermore, the produced activated carbon exhibited favourable characteristics, as indicated by a high iodine adsorption capacity and well-developed pore structure. In conclusion, activated carbon derived from duck eggshells is effective as an adsorbent for reducing FFA levels in used cooking oil and shows strong potential as an environmentally friendly and economically valuable solution.